Does the Immune System Regulate Mood to Defend against Infection? Evidence from Studies of Immune Factors, Depression, and Antidepressants - Tanaka, Midori; K. Kinney, Dennis (Current Psychiatry Reviews, 2011)
From an evolutionary perspective, psychiatric depression presents a paradox: despite disadvantages for survival and reproduction, depression has significant heritability and is remarkably prevalent. A potential explanation for this paradox is provided by the hypothesis that the immune system helps regulate mood to aid defense against infection. This “infection-defense” hypothesis proposes that immune vulnerability to infection elicits depressed mood, which in turn stimulates behaviors that help protect vulnerable individuals and their kin against infectious diseases. This paper examines evidence on predictions of the hypothesis that concern depression's relation to immune function and vulnerability to infection. A review finds support for several predictions: 1) depressed patients show elevated levels of key types of immune vulnerability; 2) in animal experiments, chronic conditions that increase vulnerability to infection also cause depressionlike behaviors; 3) there are adaptive mechanisms to fight infection that involve interactions of immune and neuroendocrine factors; 4) conditions associated with depression in humans are also associated with immune vulnerability and infection; and 5) somatic antidepressant treatments often enhance immune function and resistance to infection, with time courses of immune responses to different treatments often paralleling those for mood. 6) Finally, positive mood tends to be associated with enhanced resistance to infection. This review focuses on immune factors that are crucial for defense against infectious diseases and have been widely studied in relation to depressive symptoms and antidepressant therapies. The hypothesis has potential clinical implications for prevention and treatment of depression.
Keywords: intensity